2013
DOI: 10.1016/j.biosystems.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Modular organization of cancer signaling networks is associated with patient survivability

Abstract: Molecular signaling networks are believed to determine cancer robustness. Although cancer patient survivability was reported to correlate with the heterogeneous connectivity of the signaling networks inspired by theoretical studies on the increase of network robustness due to the heterogeneous connectivity, other theoretical and data analytic studies suggest an alternative explanation: the impact of modular organization of networks on biological robustness or adaptation to changing environments. In this study,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
3
20
0
1
Order By: Relevance
“…Recent papers [5,6] describe topological metrics of PPI cancer networks that correlate with 5-year cancer patient survival. Of particular interest are Breitkreutz et al [7] and Takemoto and Kaori [8] who introduce a thermodynamic measure based on degree distribution. A degree distribution is essentially a Boltzmann probability distribution [9,10], which allows us to consider realworld statistical thermodynamics as a conceptual framework within which to view cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers [5,6] describe topological metrics of PPI cancer networks that correlate with 5-year cancer patient survival. Of particular interest are Breitkreutz et al [7] and Takemoto and Kaori [8] who introduce a thermodynamic measure based on degree distribution. A degree distribution is essentially a Boltzmann probability distribution [9,10], which allows us to consider realworld statistical thermodynamics as a conceptual framework within which to view cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers [3,4] describe topological metrics of PPI cancer networks that correlate with 5-yr cancer patient survival. Breitkreutz et al (2012) [5] and Takemoto and Kaori (2013) [6] describe a thermodynamic measure based on degree distribution. A degree distribution is essentially a Boltzmann [7]distribution, which allows us to consider real-world thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…PPI networks are being used with increasing frequency for mining information about cancer dynamics, cancer progression and therapy, but there are no meaningful tools to analyze them. Breitkreutz et al (2012) found a correlation of degree-entropy of PPI with 5-yr survival [5] , introducing the concept, and the work was further elaborated on by Takemoto and Kaori in 2013 [6]. Thus, the concept of mathematically analyzing complexity of networks is not new.…”
Section: Introductionmentioning
confidence: 99%
“…Several data analytical studies have found a positive correlation between environmental variability and network modularity in several types of biological system (e.g. metabolic networks (Parter et al, 2007) and cancer signalling networks (Takemoto and Kihara, 2013)). Nevertheless, scepticism still exists regarding the impact of environmental variability on modularity in intracellular networks (Clune et al, 2013;Hansen, 2003;Holme, 2011;Takemoto, 2013Takemoto, , 2012.…”
Section: Introductionmentioning
confidence: 99%